Exposure to hydrogen fluoride: an experimental study in humans of concentrations of fluoride in plasma, symptoms, and lung function. Issue 1 (January 1997) - Lund, K; Ekstrand, J; Boe, J; Søstrand, P; Kongerud, J
Abstract : OBJECTIVES: To study the absorption of inhaled hydrogen fluoride (HF) by measuring plasma fluorides and HF concentrations in the breathing zone during exposure to HF. A possible dose-effect relation was investigated by following airway symptoms and lung function-that is, forced expiratory volume in one second (FEV1) and forced vital capacity (FVC)-during and after exposure to HF. METHODS: 20 healthy, male volunteers were exposed for one hour to constant HF concentrations that ranged from 0.2 to 5.2 mg/m3; these concentrations are known to occur among potroom workers in the primary aluminium industry. Plasma fluorides were analysed before, during, and after exposure. Symptoms from the eyes and the upper and lower airways were registered and graded from 1 to 5 with a standardised questionnaire. RESULTS: The total symptom score was significantly increased at the end of exposure for all the subjects as a group (P < 0.01) and for the group exposed to HF below the present Norwegian standard for total fluorides 0.6 mg/m3 (P = 0.05). No change was detected in FEV15 although a significant decrease was found in FVC in the group exposed to fluorides below the hygienic standard (n = 9) and for the entire group (n = 23). Almost all the symptoms had disappeared four hours after the end of exposure. Symptom scores from the upper airways were significantly correlated with the HF concentration (r = 0.62, P = 0.002), the change in plasma fluoride concentration (delta C) (r = 0.51, P = 0.01), and the maximum plasma fluoride concentration (Cmax) (r = 0.42, P = 0.05). A significant correlation was also found between the total symptom score for airways and the HF concentration. CONCLUSIONS: The present study showed a strong relation between inhaled HF and concentrations of fluoride in plasma. Upper airway and eye symptoms occurred after one hour of exposure to HF even when below the Norwegian hygienic standard for fluorides.